(untitled) (Szociológiai Szemle, 2024)
The study presents the characteristics of „trust economy” based on the findings of interviews conducted among countryside small entrepreneurs. There are three aspects of the issue of trust discussed: The use of written records in entrepreneurial contracts, the interdependency of networks and trust, and the attitude of small entrepreneurs towards banks. Even the written contract does not provide guarantee for the case when the business partner should violate a contract in an economic situation considered as uncertain. They do not trust the administration of justice and/or regard it as low efficiency organizations. The entrepreneurs who know each other very well and belong to the same network are the members of social relations defined by Coleman as closed social structure. Inside that entrepreneurial circle where members are within social sight, giving on credit and money lending is general practice and the agreement on that is often only verbal. The attitude of this group towards banks is negative. The exploitation of social organizations for different from there original function can turn out to be a success or can be a failure. The example for the success is the business based on the trust relationship within the church. On the other hand the effort to exploitation is a failure when in an organization there are too many members with the primary ambition of exploitation. This will not make possible the spontaneous, „organic” way of production of trust.